The Implementation of Labor Development Principles According to Job Creation Law as a Reason to Protect Wages Rights - Nur Putri Hidayah; Quincy R. Cloet; David Pradhan (BESTUUR, 2021)
Wage is a fundamental right of labor. Since the passage of the Job Creation Law, the wage policy has changed. In order to aid national development, the wage is ruled to be distributed following the principle of job creation. Instead of bringing peace, that change has led to public criticism towards the Job Creation Law, which is deemed to injure labor rights. This study aims to analyze the legal protection and the implementation of labor development principles in the Job Creation Law. This study is normative legal research and applies a juridical approach. The primary data were obtained from the regulation analysis, while the secondary data were collected from a literature review regarding wage rights. This research reveals that the legal protection of wages in the new regulation is not far better than the previous law. The wage policies initially stipulated explicitly in the Labor Law were revoked from the Job Creation Law, where the labor principles are not applied. By the protection not better than that of the former regulation, it is implausible to improve the welfare of workers and their family members.